Pengaruh Akuntabilitas, Transpransi Dan Penggunaan Alokasi Dana Desa Terhadap Kepercayaan Masyarakat Di Desa Putra Buyut Gunung Sugih Lampung Tengah - Nirmala, Maya Dwi; Hendri, Nedi; Darmayanti, Elmira Febri (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aimed at analyzing accountability (1), transparency (2), and use of the village Fund budget (3) on community trust in Putra Buyut Gunung Sugih village, Central Lampung. The population was 1144 respondents. The sampling technique was undertaken with several respondent criteria until obtaining 143 respondents. The collected data were analyzed by testing multiple linear regression analysis through the SPSS version 25 program. The results of this study showed that Accountability, Transparency and Use of the Village Fund Budget partially or simultaneously effected the Community Trust at Putra Buyut Village, Gunung Sugih, Central Lampung.